Hall current and non-linear slip impact on hydro-magneto-thermal hybrid nanofluid flow past a vertical rotating cone with sundry base fluids - Hakeem, A. K. Abdul; Kirusakthika, S.; Ganga, B.; Akilesh, M.; Dogonchi, A. S.; Nayak, M. K. (Numerical heat transfer. Part A, Applications, 2024)
The numerical investigation regarding the impact of Hall current and non-linear slip on the flow of hybrid nanofluid past a vertical rotating cone is carried out in the present study. Each hybrid nanofluid comprises two nanoparticles and two base fluids such as water and sodium alginate. The numerical solution is devised by Fourth order Runge-Kutta scheme cum shooting technique. The obtained outcomes are that tangential velocity and swirl velocity ameliorate subject to rise in magnetic parameter and Hall parameter for water and sodium alginate based hybrid nanofluids. Tangential and swirl velocities exhibit opposite subject to non-linear slip condition. Heat transfer rate attains greatest magnitude for TiO 2 + Cu/H 2 O hybrid nanofluid among all the remaining hybrid nanofluids.